ผลของ NAA และ BA ต่อการพัฒนาของชิ้นส่วนแววมยุราที่เพาะเลี้ยงต่างกันในสภาพปลอดเชื้อ - พรธนะวัฒน์ นนทกร; เตชะศีลพิทักษ์ ธัญญะ; จารุวัฒนพันธ์ ทัศไนย; จันจุฬา ณัฐพงค์; บาลลา นุชรัฐ (Thai Journal of Science and Technology, 2019)
Abstract Torenia is an ornamental plant that has received great interest in foreign countries because it can grow in many environments and bloom all year round, so it is favored to use as a garden plant and potted plant. At present, there is a study to develop new characters or new colors of Torenia. Tissue culture is a propagation method that can increase more plants in a short time and still protect the plants from insects and plant diseases. The aim of this study is to gain more background data about micropropagating of this plant using the plant growth regulators BA and NAA. Cotyledon, leaf and internode explants were cultured on ½ MS medium supplemented with NAA at concentrations ranging from 0.5-2.0 mg/L and ½ MS medium supplemented with 0.5 mg/L NAA and 0.5-2.0 mg/L BA. The number of calluses, shoots and roots were recorded after cultured for four weeks. The result showed that the explants of cotyledon, leaf and internode cultured on ½ MS medium supplemented with 2.0 mg/L NAA had the highest number of roots (15.83, 14.50 and 14.75 roots, respectively) and the biggest size of calluses (0.80, 0.92 and 0.83 cm, respectively). In addition, the explants of cotyledon, leaf and internode cultured on ½ MS medium supplemented with 0.5 mg/L NAA and 2.0 mg/L BA had the highest number of shoots (9.26, 9.41 and 8.31, respectively) and the biggest size of calluses (0.63, 0.66 and 0.69 cm, respectively). Keywords: cotyledon; leaf; internode; tissue culture